PENGARUH PAJAK DAN RETRIBUSI DAERAH TERHADAP PENDAPATAN DAERAH PEMERINTAH PROVINSI DI PULAU JAWA DAN SUMATERA - Nurwahidah M; Zainal Abidin (Universitas Muhammadiyah Makassar, 2021)
This study aims to analyze the effect of regional taxes and levies on regional revenues for the Provincial Government in the Western Region of Indonesia (KBI). This research uses descriptive quantitative research method. The object of this research is the Provincial Governments located in the Western Region of Indonesia, namely DKI Jakarta, Banten, West Java, Central Java, East Java, DI Yogyakarta, Nanggroe Aceh Darussalam, North Sumatra, West Sumatra, Riau, Riau Islands, Jambi, Bengkulu, South Sumatra, the Bangka Belitung Islands and Lampung. The data used is the Regional Government Financial Report for the 2016-2020 fiscal year (5 years). The results of the study indicate that regional taxes and levies have a significant effect on the regional income of the provincial government. Partially, local taxes have a positive and significant effect on regional income while regional levies have a negative but not significant effect on regional income for provincial governments in Western Indonesia